Description of Upper Extremity Muscle Strength In Patients Post Stroke in The Working Area of The Sidoarjo Community Health Center - Afifah, Yulia Ayu; Widarti, Luluk; Suprianto; Hariono (Global Ten Public Health and Nursing Journal, 2024)
Stroke is a functional disorder of the brain caused by blocked blood vessels in the brain which reduces the supply of oxygen and nutrients to the brain. Decreased muscle strength often occurs in stroke patients. Muscle strength is the ability of the muscles to perform one full contraction against resistance or load. The purpose of this study was to describe the strength of the upper extremity muscles in post-stroke patients in the working area of the Sidoarjo Health Center. The research method used is descriptive. The sampling technique in this study used a quota sampling technique with a sample of 30 people. The data collection tool uses the Medical Research Council Muscle Scale muscle strength scale. The results showed that data obtained for upper extremity muscle strength in lifting as much as 23% with a right hand muscle strength scale of 3 and 27% with a left hand muscle strength scale of 0 and upper limb muscle strength in grasping as much as 20% with a right hand muscle strength scale of 3 and 27%. with the left hand muscle strength scale 3. It is hoped that the patient can do range of motion exercises so that the joints are not stiff.